100gm Pouch Food Holder - Sukindar, Nor Aiman; Yang, Chuan Choong; Ahmad Azhar, Ahmad Zahirani; Kamaruddin, Shafie; Mel, Maizirwan (2021)
Food holder is the tool used in the food manufacturing industry, especially for retort technology for holding the food packaging in the filling line. The unique design of every food packaging size determines the efficiency of the production line. The specific height, slotting dimension and elbow height is the most critical part to ensure the food holder works efficiently.